Distribuição espacial de Biomphalaria sp e sua influência na infecção humana por Schistosoma mansoni no município de Ilha das Flores, Sergipe - Barboza, Delmany Moitinho (2011)
Spatial distribution of Biomphalaria sp and its influence on human infection by S. mansoni in the municipality of Ilha das Flores, Sergipe. Barboza DM, Aracaju - Sergipe, 2011. The expansion of schistosomiasis is directly linked to the spatial distribution of intermediate hosts of S. mansoni, in the northeast of Brazil are snails of the genus Biomphalaria, B. glabrata and B. straminea. The aim of this study was to investigate the spatial distribution of Biomphalaria sp in an endemic area for schistosomiasis and to evaluate the relationship between irrigation, natural water sources, water contact and the of human infection intensity with S. mansoni. This was a cross-sectional epidemiological study, conducted in the municipality of Ilha das Flores, one of the largest producers of the rice in the state of Sergipe, located in the Lower San Francisco, on the banks of the Rio San Francisco. Malacological survey, parasitological examination and a questionnaire with data water sources exposure was conducted in the inhabitants of this municipality. The Geographic Information System was used to map the distribution of Biomphalaria sp and water sources. The georeferenced database was created in the software SPRING 5.0 and ArcGIS 9.3. The photo-interpretation of the area was carried out using aerial photographs and images of the Sino-Brazilian satellite CBERS 2B. The images and photos georeferencing of was made through the acquisition of control points acquired in the field with Global Positioning System (GPS). We identified two species of Biomphalaria in the endemic area, and the B. glabrata found more and more infected than B. straminea. The malacological study results show a competitive selection among species of Biomphalaria with a predominance of B. glabrata in water sources related to the irrigation system and B. straminea in natural water sources. We observed a direct correlation between the intensity of human infection and human contact with water sources related to irrigation. We conclude that the rice cultivation and irrigation systems have an impact on human infection with S. mansoni.